Oil spills - Blashfield, Jean F.; Black, Wallace B. (Chicago : Childrens Press, 1991)
Describes how an oil spill occurs; the damaging effects of recent spills on the sea, land, and wildlife; and the difficult process of cleaning up after a spill.
Includes index.
Booklist.
School Library Journal.
7.4
5-8
Keywords: Oil spills -- Environmental aspects -- Juvenile literature; Oil spills; Pollution; Oil spills; Pollution